Entrepreneurship Education: State of the Art - Sánchez García, José Carlos (2017)
Job uncertainty and ambiguity is a reality in many current societies, therefore, the idea of self-employment has taken a more active role, not only out of necessity, but also because it brings innovation and development to societies. In view of this situation, the following question arises: how can we strengthen the entrepreneurial spirit of our students? This article has the objective to collect theoretical information of the state of the art on entrepreneurship education: what it has been, what it is, and what can it be, in order to present the current condition of the topic, both in the psychological and pedagogical field. To achieve this objective, information from 108 research sources, mainly from scientific articles and books was collected, concluding that, although generally, entrepreneurship education has significantly contributed to the creation of businesses, developing countries, specifically, those in Latin America, still require extra effort to fully implement entrepreneurship topic in the curriculums, particularly because of challenges such as political instability, technology and international competition.